STUDI LITERATUR: KINERJA KEUANGAN DAERAH - Ayu Rohanda (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2022)
The aim of the research was to identify regional financial performance which is influenced by regional original income, general allocation funds, special allocation funds and regional expenditures. Regional financial performance is generally measured using financial ratios in the form of independence ratios and can also use efficiency ratios. Research methods for literature studies that examine articles related to regional financial performance. The data used is second party data, namely previous research. The results obtained from previous research found that financial performance is influenced by local original income, where the increasing local original income, the better the regional financial performance. Then the general allocation funds and special allocation funds show a negative effect on regional financial performance, this is because the greater the regional revenue from the central government, the less independent a region is. In addition, regional spending has an effect on regional financial performance, this is because with regional spending, an area can develop and provide welfare to its people.